Mastering cross-platform development with Xamarin : master the skills required to steer cross-platform applications from drawing board to app store(s) using Xamarin /: master the skills required to steer cross-platform applications from drawing board to app store(s) using Xamarin. (2016) - Bilgin, Can
No abstract available